2016
DOI: 10.15287/afr.2016.692
|View full text |Cite
|
Sign up to set email alerts
|

Forest vegetation in western Romania in relation to climate variables: Does community composition reflect modelled tree species distribution?

Abstract: Abstract. European beech (Fagus sylvatica L.) is the prevailing tree species of mesic forests in Central Europe. Increasing summer temperatures and decreasing precipitation, as climate change scenarios predict, may, however, negatively influence beech growth and induce a shift to more thermophilous forest communities. Temperatures as expected in the future for western Central Europe are currently found in parts of western Romania. In light of this climate analogy we investigated forest vegetation as an indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Earlier studies of forest structure and community composition in the western Romanian study region have shown that the beech forests are in many structural aspects very similar to Central European beech forests of the Galio-Fagion, and the oak-rich forests resemble Central European communities of the Quercetalia pubescenti-petraeae (thermophilic mixed oak forests) and Carpinetalia betuli (oak-hornbeam forests), despite the admixture of additional tree species with sub-Mediterranean and southeast European origin (Heinrichs et al, 2016;Indreica et al, 2017Indreica et al, , 2019Walentowski et al, 2015). The forest inventory and soil chemical data show that the three transects are located on mesic to eutric soils, and they are more or less comparable amongst the transects.…”
Section: Climatic Conditions Across the Beech-oak Ecotonementioning
confidence: 88%
“…Earlier studies of forest structure and community composition in the western Romanian study region have shown that the beech forests are in many structural aspects very similar to Central European beech forests of the Galio-Fagion, and the oak-rich forests resemble Central European communities of the Quercetalia pubescenti-petraeae (thermophilic mixed oak forests) and Carpinetalia betuli (oak-hornbeam forests), despite the admixture of additional tree species with sub-Mediterranean and southeast European origin (Heinrichs et al, 2016;Indreica et al, 2017Indreica et al, , 2019Walentowski et al, 2015). The forest inventory and soil chemical data show that the three transects are located on mesic to eutric soils, and they are more or less comparable amongst the transects.…”
Section: Climatic Conditions Across the Beech-oak Ecotonementioning
confidence: 88%
“…by excluding unsuitable records from isolated sub-populations. Another procedure to improve extrapolation results involves the restriction of the model area, to train the model only on the cells having a common climatic range on both islands, as applied in other studies (Heinrichs et al 2016;Horsák et al 2010). We found no significant improvement in the model's predictions, due to data abatement and to loss in the ecological response curves of the training data and therewith support the findings of other studies (Thuiller et al 2004).…”
Section: The Role Of Shifting Ecological Behaviour Of Species In Modelssupporting
confidence: 82%
“…The CMI is more meaningful in climate change studies compared to other habitat suitability indices (HSI - Mellert et al 2016) as it distinguishes between the rear and the leading edge of the climatic range for a species. Recently, it has been used in many studies (Mellert et al 2015, Heinrichs et al 2016, Dorado-Liñán et al 2019, Walentowski 2019, Kasper et al 2021, Sánchez De Dios et al 2021). The CMI obtained in this study allowed a subdivision of the species niches into five meaningful zones along the gradient from the rear to the leading edge (see Fig.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%